Burden of severe neonatal jaundice: a systematic review and meta-analysis. Issue 1 (25th November 2017) - Slusher, Tina M; Zamora, Tara G; Appiah, Duke; Stanke, Judith U; Strand, Mark A; Lee, Burton W; Richardson, Shane B; Keating, Elizabeth M; Siddappa, Ashajoythi M; Olusanya, Bolajoko O
Abstract : Context: To assess the global burden of late and/or poor management of severe neonatal jaundice (SNJ), a common problem worldwide, which may result in death or irreversible brain damage with disabilities in survivors. Population-based data establishing the global burden of SNJ has not been previously reported. Objective: Determine the burden of SNJ in all WHO regions, as defined by clinical jaundice associated with clinical outcomes including acute bilirubin encephalopathy/kernicterus and/or exchange transfusion (ET) and/or jaundice-related death. Data sources: PubMed, Scopus and other health databases were searched, without language restrictions, from 1990 to 2017 for studies reporting the incidence of SNJ. Study selection/data extraction: Stratification was performed for WHO regions and results were pooled using random effects model and meta-regression. Results: Of 416 articles including at least one marker of SNJ, only 21 reported estimates from population-based studies, with 76% (16/21) of them conducted in high-income countries. The African region has the highest incidence of SNJ per 10 000 live births at 667.8 (95% CI 603.4 to 738.5), followed by Southeast Asian, Eastern Mediterranean, Western Pacific, Americas and European regions at 251.3 (132.0 to 473.2), 165.7 (114.6 to 238.9), 9.4 (0.1 to 755.9), 4.4 (1.8 to 10.5) and 3.7 (1.7 to 8.0), respectively. The incidence of ET per 10 000 live births was significantly higher for Africa and Southeast Asian regions at 186.5 (153.2 to 226.8) and 107.1 (102.0 to 112.5) and lower in Eastern Mediterranean (17.8 (5.7 to 54.9)), Americas (0.38 (0.21 to 0.67)), European (0.35 (0.20 to 0.60)) and Western Pacific regions (0.19 (0.12 to 0.31). Only 2 studies provided estimates of clear jaundice-related deaths in infants with significant jaundice [UK (2.8%) and India (30.8%). Conclusions: Limited but compelling evidence demonstrates that SNJ is associated with a significant health burden especially in low-income and middle-income countries.